Bone regeneration in calvarial defects of NOD.CB17-Prkdcscid/J (NOD SCID) mice from dental pulp stem cells: a systematic review - Valenzuela-Ramos, Marisel Roxana; Barrios-Sayritupac, Margarita Medaly; Chacaltana-Limaco, Ruth Daniela; Espinoza-Mendoza, Milagros Jesús; Canales-Sermeño, Gustavo (Revista Facultad de Odontología Universidad de Antioquia, 2022)
Introduction: human dental pulp stem cells show a very significant osteogenic capacity, allowing the formation of new bone that is very well adapted to existing bone. The objective was to evaluate the efficacy of bone regeneration from dental pulp stem cells, analyzing in vivo studies carried out in immunocompetent NOD.CB17-Prkdcscid/J (NOD SCID) mice. Methods: we analysed studies from 2016 to 2020, found in Pubmed, ScienceDirect and Lilacs. The systematic review followed the PRISMA guidelines, the quality and risk of bias assessment was performed considering the criteria set out in the National Heart Lung and Blood Institute - NHLBI tool. Results: applying the inclusion and exclusion criteria, 6 studies were selected and evaluated, and only 2 of them were selected for review (n=1859). Data from the studies were extracted and sorted according to study details, analysis methodology and results. Conclusion: the results obtained show that there is bone regeneration by stem cells derived from dental pulp, because they promote osteogenesis and the new bone successfully joins the existing bone. In vitro analysis indicates that it is an excellent osteogenic source and in vivo studies confirm that culture media interfere with bone formation. Further studies are required to confirm bone formation by Dental Pulp Stem Cell - DPSC. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />